(untitled) - Wormer, Katherine Van; Katherine van Wormer (Chicago, 1995)
This book provides an ecosystems approach to alcoholism and its treatment. It bridges the gap between the twelve-step approach and the scientifically based Responsibility model. Van Wormer views the individual behavior. Biological and psychological factors in alcoholism are covered. The text draws upon literature from several cultures to discuss the role of alcohol in society. Gender, minority, and gay-lesbian issues are integrated throughout
Keywords: Social work with alcoholics; Alcoholics